Dampak Cyberbullying di Kalangan Mahasiswa dalam Perspektif Maqasid Syariah - Bela Meydarista; Eka Ramalia; Dilla Septiani; Nengsih Ari Saputri; Andini salsabila; Sri Mulyani (CV. Doki Course and Training, 2026)
This study aims to analyze the phenomenon of cyberbullying among university students and examine its impact from the perspective of maqāṣid al-syarī‘ah. The study used mixed methods with a quantitative approach through a survey of 100 students of the Faculty of Sharia and Law of UIN Raden Fatah Palembang, and a qualitative approach through normative analysis of Islamic literature. Data were analyzed using descriptive statistics and content analysis techniques. The results showed that 48% of respondents had been victims of cyberbullying, 80% had witnessed it, and 32% admitted to having been perpetrators. The most dominant forms were body shaming and flaming. The main contributing factors were environmental normalization, venting of personal problems, and motivation to gain power and attention. The impacts include mental health disorders, decreased academic performance, loss of self-confidence, social disruption, and psychological trauma. In the perspective of maqāṣid al-syarī‘ah, cyberbullying is proven to violate five main principles: ḥifẓ al-dīn through the degradation of moral values, ḥifẓ al-nafs through threats to mental health, ḥifẓ al-‘aql through intellectual dysfunction, ḥifẓ al-nasl through the damage to social relations and the quality of generations, and ḥifẓ al-māl through the potential loss of productivity and the economy. This research contributes to expanding the study of maqāṣid al-syarī‘ah into the context of contemporary digital ethics, and emphasizes that cyberbullying is a form of mafsadah that must be prevented through educational, normative, and social approaches based on Islamic values.